The Economic and Social Value of Science and Technology Parks. The Case of Tecnocampus - Torres-Pruñonosa, Jose; Raya, Josep Maria; Dopeso-Fernández, Roberto (Frontiers in Psychology, 2020)
This paper aims to measure both the economic and social value of Tecnocampus, a Science and Technology Park in its region of influence (Mataró city in the Maresme region of Catalonia, Spain). Our results show that the impact of Tecnocampus has a socio-economic cost- benefit ratio of 2.39. Measuring the impact of this multifaceted centre requires a diverse approach. Although the methods used are not new, the combination of them presents a novel approach to measure the impact of an institution of this nature. We have measured the economic value with the Input-Output (IO) model, including the Social Accounting Matrix (SAM). On the other hand, for social value calculations we have used Cost-Benefit Analysis (CBA) adding measurements of firm localisation to estimate externality effects. Our main results present an economic value of more than 0.054% of the Catalan GDP, whereas the employment impact represents almost 0.37% of total employment in the region. The total economic multiplier of Tecnocampus activity is estimated to be 1.89. Social value generates an additional 0.50 euros to the multiplier according with our analysis. This additional social value represents an increase of productivity estimated in 20 million euros of operational income for Catalan firms and the creation of 7 additional firms in the Maresme region as a result of knowledge spill-overs. The social value also includes reduction of over-education caused by a better matching between graduates and enterprises, a more direct application of research and an increase in consumer surplus. Finally, we discuss the policy implications of our findings to promote investments in this kind of infrastructures.